The architecture of innovative apprenticeship - Deitmer, Ludger [Herausgeber]; Hauschildt, Ursel [Herausgeber]; Rauner, Felix [Herausgeber]; Zelloth, Helmut [Herausgeber] (Springer Science + Business Media, 2013)
"Benefiting from the support and involvement of two major international research networks, this collection features the latest research findings in TVET. Members of INAP, the International Network on Innovative Apprenticeship, and VETNET, the Vocational Education and Training Network, have contributed key research findings to this detailed survey of the field. Featuring the inclusion of the internationally recognized memorandum released in April 2012 by the INAP Architecture Apprenticeship Commission, the volume covers a wealth of issues relating to technical and vocational education and training, including exemplar architectures such as successful school-to-work transitions, competence assessment and development models, and governance, including the role of stakeholders. The book provides many opportunities to explore in depth the scholarly debate on TVET, as well as to learn from positive international experiences. It aims to inform the practice of TVET professionals as much as the decision making of administrators." (Hrsg., BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; T 1.5 International vergleichende Berufsbildungsforschung; Berufsbildungssystem; Berufseinmündung; Internationaler Vergleich